2008
DOI: 10.1111/j.1365-2400.2008.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐sea power cables and the migration behaviour of the European eel

Abstract: Coded acoustic tags and an array with moored receivers were used to study the effect of a sub-sea AC power cable on migrating European eel, Anguilla anguilla (L.) in the Baltic Sea. Sixty eels were tagged and the migration speed was measured in a strait with a 130 kV AC power cable. Observed swimming speed over the ground was corrected for advection by the water current. Eel swimming speed was significantly lower around the cable than both north and south of the cable. No details on the behaviour during passag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…Noise from the turbines may potentially increase stress levels in fish or harm internal communication by masking sound signals used by the fish (Andersson 2011, Popper & Hawkins 2012). Changes in electromagnetic fields may de crease foraging efficiency in species that use their electromagnetic sense for detecting prey, such as elasmobranchs (Kimber et al 2011, Gill et al 2012, or potentially disturb fish migration (Wes terberg & Begout-Anras 2000, Westerberg & Lagenfelt 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Noise from the turbines may potentially increase stress levels in fish or harm internal communication by masking sound signals used by the fish (Andersson 2011, Popper & Hawkins 2012). Changes in electromagnetic fields may de crease foraging efficiency in species that use their electromagnetic sense for detecting prey, such as elasmobranchs (Kimber et al 2011, Gill et al 2012, or potentially disturb fish migration (Wes terberg & Begout-Anras 2000, Westerberg & Lagenfelt 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the few field studies on the behavior of fishes in the presence of human-induced EMF in submarine power cables are, at best, equivocal. The swimming speed of European eel, Anguilla anguilla, passing over a 130 kV AC power cable in the Baltic Sea was observed [22] and a small effect was found with eels slowing their swimming speed when both approaching and exiting from the cable region. However, there was no statistically significant relationship between the amperage in various parts of the cable and swimming speed.…”
Section: Discussionmentioning
confidence: 99%
“…Gill et al [79] identified eight migratory fish species sensitive to electromagnetic fields, including the European eel Anguilla anguilla, the Atlantic salmon Salmo salar and the Yellowfin tuna Thunnus albacares. Limited in situ data are available about the actual effects on fish, which rely on magnetic fields for migration; however, several studies in the Baltic Sea have indicated that the swimming speed of European eels is reduced in the vicinity of underwater electric cables [78,80]. However, due to the limited availability of empirical studies, it is difficult to theorize the extent of the impacts that electro-magnetic fields have on Mediterranean marine species and their fecundity.…”
Section: Potential Effects On Mediterranean Fish Communitiesmentioning
confidence: 99%